2015
DOI: 10.1088/0004-637x/810/1/64
|View full text |Cite
|
Sign up to set email alerts
|

Can Direct Collapse Black Holes Launch Gamma-Ray Bursts and Grow to Supermassive Black Holes?

Abstract: The existence of black holes (BHs) of mass ∼ 10 9 M ⊙ at z 6 is a big puzzle in astrophysics because even optimistic estimates of the accretion time are insufficient for stellar mass BHs of ∼ 10 M ⊙ to grow into such supermassive BHs. A resolution of this puzzle might be the direct collapse of supermassive stars with mass M ∼ 10 5 M ⊙ into massive seed BHs. We find that if a jet is launched from the accretion disk around the central BH, the jet can break out the star because of the structure of the radiation p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 74 publications
3
48
0
Order By: Relevance
“…[28] (see Eqs. (25)(26)(27) for this reference). We also simulated the gravitational collapse including the effect of the rpprocess as test calculations and found that the rp-process affects only weakly the gravitational collapse because this process becomes efficient only in the very dense and hot region.…”
Section: Equation Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…[28] (see Eqs. (25)(26)(27) for this reference). We also simulated the gravitational collapse including the effect of the rpprocess as test calculations and found that the rp-process affects only weakly the gravitational collapse because this process becomes efficient only in the very dense and hot region.…”
Section: Equation Of Statementioning
confidence: 99%
“…Our previous study [23] proposed that if a SMS core is rotating, gravitational waves associated with the quasi-normal mode ringdown are emitted during the black-hole formation and if it occurs at the cosmological redshift less than ≈ 3, the signal will be detectable by space laser interferometric detectors like LISA [24]. Other studies show that a collapsing SMS may be detectable as a gamma-ray burst or an ultra-luminous supernova if the formed black hole launches a relativistic jet during the collapse [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus we conclude that it will be difficult for Pop-III HNRs to dominantly contribute to the observed high-energy backgrounds unless the explosion energy is E Pop−III 10 53 erg. On the other hand, the explosion energy for supermassive stars at very-high-redshifts could be larger than ∼ 10 55 erg (Matsumoto et al 2015). Note that the relative ratio of the neutrino fluxes contributed by the high and low redshift components are largely uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to understand how these early SMBHs formed over such short time-scales, and there are open issues with various plausible scenarios (e.g., Dijkstra et al 2008;Mayer et al 2010;Inayoshi & Omukai 2012;Tanaka & Li 2014;Matsumoto et al 2015). The presence of massive BH seed candidates (10 5 M⊙ at z > 6), possibly direct collapse black holes, in a bright Lyman-α emitter at z = 6.6 have been recently suggested (Smith, Bromm & Loeb 2016;Pacucci et al 2017).…”
Section: Introductionmentioning
confidence: 99%